Folic Acid–Functionalized Composite Scaffolds of Gelatin and Gold Nanoparticles for Photothermal Ablation of Breast Cancer Cells - Chen, Huajian; Wang, Xiuhui; Sutrisno, Linawati; Zeng, Tianjiao; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping (Frontiers in Bioengineering and Biotechnology, 2020)
Photothermal therapy (PTT) has been developed as a useful therapeutic method for cancer treatment. Localization of PTT agents in cancer sites and targeting capacity are required to further increase therapeutic efficacy. In this study, gold nanoparticles (AuNPs) and gelatin were functionalized with folic acid (FA) and hybridized to prepare FA-functionalized gelatin-AuNPs composite scaffolds. AuNPs with rod- and star-shape of three sizes (40, 70 and 110 nm) were used for the hybridization to investigate the influence of AuNPs shape and size. The composite scaffolds showed porous structures with good interconnectivity. Modification with FA increased capture capacity of the composite scaffolds. Hybridization with AuNPs rendered the composite scaffold a good photothermal conversion property under NIR laser irradiation. Temperature change during laser irradiation increased with the laser power intensity and irradiation time. The shape and size of the AuNPs also affected their photothermal conversion property. The composite scaffold of gold nanorods 70 (FA-G/R70) had the highest photothermal conversion capacity. Breast cancers cultured in the FA-G/R70 composite scaffold were killed under NIR laser irradiation. Mouse subcutaneous implantation further demonstrated the excellent photothermal ablation capability of the FA-G/R70 composite scaffold to breast cancer cells. The FA-functionalized composite scaffolds were demonstrated a high potential for local PPT of breast cancer.